Ḥadd-i rajm kī sharʻī ḥais̲iyyat aur shubhāt o mugẖāla̤tāt kā jāʼizah - Yūsuf, Salāḥuddīn (Silsilah-yi ishāʻat-i Dāruddaʻvat as-Salfiyah, 1981)
A defence of the Islamic law of 'rajm' (stoning adulterers to death); Ahl-i Hadith viewpoint.